It`s okay to be a quad: Wheelchair rugby players` sense of community - Goodwin, D.; Johnston, K.; Gustafson, P.; Elliott, M.; Thurmeier, R.; Kuttai, H. (Adapted Physical Activity Quarterly, 2009)
This study explored the social experience of wheelchair rugby from the perspective of the players. Eleven national level rugby players (10 males, 1 female with a mean age of 33 years) shared their experiences through the phenomenological methods of semistructured focus group interviews and artifacts. Three themes emerged from the thematic analysis (a) it`s okay to be a quad, (b) don`t tell us we can`t, and (c) the power of wheelchair rugby. The athletes identified with a shared sense of community and the membership, fulfillment of need, influence, and shared emotional connections they used to authentically express themselves through their sport. The implications of the findings were interpreted within the theoretical context of psychological sense of community.